The Relationship of Socioeconomic Status with Motivation for Learning in Religious Studies at SMA Advent Nabire - Andrian Erich Steven Arfayan; Juwinner Dedy Kasingku (Universitas Muhammadiyah Enrekang, 2023)
The socioeconomic status of parents can be a factor affecting students' learning motivation. If a child's learning facility needs are not met due to the socioeconomic status of their parents, it may potentially impact the child's learning motivation. This study involves two variables: the independent variable (the variable that influences other variables) is socioeconomic status, and the dependent variable (the variable influenced by other variables) is the learning motivation in religious studies. This research uses the quantitative-descriptive correlation. Data collection was done using both population and sample methods. The researcher used the mean score to determine the level of parents' socioeconomic status and the level of student motivation in religious studies. Furthermore, the study aimed to ascertain whether there is a significant relationship between socioeconomic status and learning motivation in religious studies at SMA Advent Nabire, using Pearson correlation. The results of the research conducted at SMA Advent Nabire, Papua, indicate that the level of parents' socioeconomic status is moderate with a mean of 2.89 (rounded from 2.8807), and students' learning motivation in religious studies is moderate with a mean of 3.22 (rounded from 3.2135). Additionally, the study at SMA Advent Nabire, Papua, shows that there is no significant relationship between parents' socioeconomic status and students' learning motivation in religious studies. This conclusion is based on the calculation result with p-value = 0.543, which is greater than α = 0.05, and a correlation value of -0.073, which is less than the table value of 0.227.